Gastrotracheal Fistula as a Result of Transhiatal Esophagectomy for Esophageal Cancer: An Unusual Complication - Heshmatollah Salahi; Mehdi Tahamtan; Bijan Ziaian; Mansoor Masjedi; Zahra Saadati; Nazanin Hoseini; Elahe Torabi (Case Reports in Surgery)
Gastrotracheal fistula following open transhiatal esophagectomy (Orringer’s technique) for esophageal cancer is an unusual but lethal complication. Surgical intervention with resection of the fistula tract and primary interrupted suturing of gastric and tracheal orifices using a muscle flap interposition has proved to be a successful method. We report the case of a 73-year-old male with an adenocarcinoma of the distal part of the esophagus, who underwent open transhiatal esophagectomy (Orringer’s technique) with gastric tube reconstruction and cervical anastomosis. The patient did not receive induction chemoradiotherapy before the esophagectomy. Two attempts of surgical repair of fistula failed and the patient died. Being aware of warning signs such as dyspnea and respiratory distress accompanied by bilious content in the tracheal tube is helpful in the early detection and treatment of this type of fistula.